School dropout among orphans in Oshana region - Namibia - Ishola, Anthony; Mitonga, Kabwebwe Honore (International Journal of Health, 2016)
This research seeks to investigate why some orphaned children drop out of school in Oshana region, Namibia, despite concerted efforts by the Government Republic of Namibia and other stake holders to keep them at school.The study aimed to identify the indicators preceding AIDS orphaned children dropping out of schools in the Oshana region-Namibia. A cross-sectional study, which adopted both quantitative and qualitative approaches, was used to gain a complete picture of the situation of orphans and school dropouts from the perspective of school teachers, learners, and orphans who have already dropped out of school. It was found that many orphans still face many challenges and to some, continuing with schooling is a luxury that is ill afforded. The total percentages of learners that dropped out of school are: 52.9% orphans in grades 7 and 8 in 2009 while 41.7% dropped out in 2010. Poor awareness of Government support initiatives, poor psychosocial support, leaving school to grieve the death of a parent and working to earn income, ranked amongst the highest reasons some orphans dropped out of school. Provision of material resources in addition to human torch as demonstrated by majority of life skill teachers towards the well-being of AIDS orphans have greatly ameliorated the self-worth and schooling of orphans.